PELANGGARAN PRINSIP KERJASAMA DALAM NOVEL 5 CM KARYA DONNY DHIRGANTORO - Rini Veronika; Mangatur Sinaga; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the violation of the principles of cooperation, and the implications contained in the novel 5 cm Donny Dhirgantoro work. This study aimed to describe violations of the principle of cooperation and implications maxim maxim violation in a novel 5 cm Donny Dhirgantoro work. This research is helpful in a practical, theoretical, and educative. The theory used in this research one theory Jacob L. Mey (in Rahardi, 2005: 49) pragmatics is the science which studies language usage conditions of human language that basically is determined by the context and background of the language that embodies it. Furthermore, there is also a theory of Karl Buhler (in Ullmann, 2007: 15) points out three aspects of language from the perspective of the speaker, the speech act is a symptom (symptom), which is a hint or indication about what is or what is going on in his mind, from the point viewing audience, the speech act is a signal (signal) that call or order him to do something acts and from the point of communication itself speech act is a symbol (symbol), which is a sign indicating anything intended by the speaker to be delivered and wrong one important thing in a pragmatic interpretation of the conversation, the concept of linking meaning and context of the conversation is the concept of speech acts (speech acts), a concept developed by Austin (in Nurgiyantoro, 2013: 425). This study is a qualitative research and descriptive method. Techniques used in data collection in this study is engineering documentation and technical notes. Data that has been found by reading and then analyzed by several stages, which collects sentences, selecting, classifying, implies a violation of maxims, and make conclusions. Data breach the principle of cooperation found comes from the novel is used as a reference in the study. The amount of the overall data in the study of ninety-three data. Sixty-four data breach maxim of quantity, quality maxim of six data breach, fifteen data breach maxim of relevance, and eight data breach maxim way or execution. The object of this study is the word which violations of the principle of cooperation. The results of this study as a contribution for further research regarding the violation of the principle of cooperation.Key Words: Violation of principle, Cooperation, Novel.